Enthalpies of formation of the solid solutions of ZrxY0.5−x/2Ta0.5−x/2O2 (0 ≤ x ≤ 0.2 and 0.65 ≤ x ≤ 1). Issue 19 (14th October 2019) - Lepple, Maren; Lilova, Kristina; Levi, Carlos G.; Navrotsky, Alexandra
Abstract: Abstract : Enthalpies of formation and heat capacities are key parameters for thermodynamic assessments using the CALPHAD method and were determined in this work in the ZrO2 –Y0.5 Ta0.5 O2 quasibinary system. Zr x Y0.5− x /2 Ta0.5− x /2 O2 samples with compositions in the monoclinic and tetragonal ZrO2 -based solid solutions (0.65 ≤ x ≤ 1) as well as the two monoclinic (M′ and M) polymorphs of the Y0.5 Ta0.5 O2 -based solid solutions (0 ≤ x ≤ 0.2) were investigated. The enthalpies of the two monoclinic polymorphs M′ and M are essentially the same within experimental uncertainty and have significant energetic stability (enthalpies of formation near −45 kJ/mol) relative to their component oxides. The monoclinic and tetragonal zirconia-rich solid solutions have little energetic stability with respect to ZrO2, Ta2 O5, and Y2 O3 and presumably owe their existence to the configurational entropy. The heat capacities of M′ and M phase are similar and can be estimated from their constituent oxides using the Neumann–Kopp rule.